Gait impairments in patients with bilateral vestibulopathy and chronic unilateral vestibulopathy - Boutabla, Anissa; Revol, Rebecca; Carvalho, Marys Franco; Grouvel, Gautier; Corre, Julie; Cugnot, Jean-François; Cavuscens, Samuel; Ranieri, Maurizio; Zhu, Meichan; McCrum, Christopher; van de Berg, Raymond; Armand, Stéphane; et al. (Frontiers in Neurology, 2025)
Vestibular deficits often lead to unsteady gait, affecting quality of life and increasing fall risk. This study aimed to identify gait impairments in chronic vestibulopathy. Ten patients with bilateral vestibulopathy (BV), 10 patients with chronic unilateral vestibulopathy (UV), and 10 healthy participants (HS) participated. Spatio-temporal parameters were computed during walking at various self-selected walking speeds (slow, comfortable, and fast) using motion capture system with additional assessment usingclinical gait tests [functional gait assessment (FGA), tandem walk (TW), Timed Up and Go test (TUG)], and symptom severity [Dizziness Handicap Inventory (DHI)] were assessed and compared between the three groups. BV and UV patients showed significantly slower walking speeds, shorter step lengths, and broader step widths compared to HS, but similar cadence. Significant differences were also seen in stance phase, double and single support phases at comfortable and slow speeds, but not at fast speed. BV patients, but not UV patients, had worse FGA scores than HS, reflecting their reported difficulties in specific tasks requiring greater postural control. Tandem walk performance was lower in BV patients compared to the other groups, whereas there was no significant differences in TUG scores. Cluster analysis revealed two distinct clusters: one with all HS and most UV patients (70%), and another with most BV patients and 30% of UV. Overall, this study highlights how altered vestibular function impacts gait outcomes. These findings can aid clinicians in evaluating gait in patients with vestibular deficits and monitoring rehabilitation interventions.